2017
DOI: 10.1534/g3.116.038075
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Transcriptome Approach to Evaluating Reference Genes for Quantitative Gene Expression Studies: A Case Study in Mimulus

Abstract: While quantitative PCR (qPCR) is widely recognized as being among the most accurate methods for quantifying gene expression, it is highly dependent on the use of reliable, stably expressed reference genes. With the increased availability of high-throughput methods for measuring gene expression, whole-transcriptome approaches may be increasingly utilized for reference gene selection and validation. In this study, RNA-seq was used to identify a set of novel qPCR reference genes and evaluate a panel of traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…(A) Alignment of MYB5a , MYB5b , and MYB4 . Amino acid sequences were inferred by translating DNA sequences, obtained from the M. l. luteus genome and transcriptome ( Edger et al 2017 ; Stanton et al 2017 ) and from PCR and Sanger sequencing of M. l. variegatus . Black rectangles identify putative Subgroup 6 motifs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(A) Alignment of MYB5a , MYB5b , and MYB4 . Amino acid sequences were inferred by translating DNA sequences, obtained from the M. l. luteus genome and transcriptome ( Edger et al 2017 ; Stanton et al 2017 ) and from PCR and Sanger sequencing of M. l. variegatus . Black rectangles identify putative Subgroup 6 motifs.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extractions, cDNA synthesis, and endpoint RT-PCR were performed as described in the Expression Analyses section, to evaluate the expression of the target gene relative to an untransformed control plant. Two different primer pairs targeting MYB5a were used, 33 F-40R and 44 F-45R, along with primers to reference gene GAPDH ( Stanton et al 2017 ) as a positive control (Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, four housekeeping genes ( GAPDH, actin, tubulin , and 18S ) and other four genes ( TBP, SAM, HSP90 , and MUB ) were used as query genes for the blast against the RNA-seq data (Yang et al, 2017) to find the homologous genes (Stanton et al, 2017). Genes with similar expression levels in four different tissues were selected as candidates as previously reported (Tan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports of selection and validation of reference genes in model plant species including Arabidopsis thaliana 20 , Oryza sativa 30 , Helianthus annuus 31 , Triticum aestivum 32,33 , Zea mays 34 and Glycine max 35 . The list also includes diverse non-model plant species including flax 36 , white clover 37 , bamboo 38 , peach 39 , Mimulus 40 , watermelon 41 , grape vine 42 , and lettuce 43 . However, in most of these cases the selection of suitable reference gene(s) was based on tightly controlled experimental conditions, whereas it has been reported that the expression of these gene(s) can vary in different tissues under different experimentally controlled conditions 26,4448 .…”
Section: Introductionmentioning
confidence: 99%